Effects of the North Atlantic Oscillation (NAO) and meteorological variables on the annual Alcarria honey production in Spain - Salvo-Tierra, Ángel Enrique; Báez, José Carlos; García-Soto, Carlos; Real-Giménez, Raimundo; Márquez-Moya, Ana Luz; Flores-Moya, Antonio (Taylor & Francis, 2019)
La Alcarria is one of the most significant regions for honey production in Spain. Times series data of the annual Alcarria honey production from 2000 to 2013 revealed that the total production was highly variable ranging from ca. 60,000 kg in 2000 to almost three times as much in 2011, but without a remarkable trend through time. We hypothesized that these local fluctuations in honey production may be explained by broad-scale climatic patterns. Based on the multiple linear models, we found a significant positive relationship between honey production as a function of the overall means of the North Atlantic Oscillation (NAO) index and precipitation in January, which accounts for 80% of the variability in the Alcarria honey production. We propose that the effect of a negative phase of the NAO and precipitation in January could predict the Alcarria honey production a few months in advance.
Keywords: Apicultura; La Alcarria - Clima - Observaciones; Alcarria honey; North Atlantic Oscillation; precipitation